Characteristic Cytokine Profiles of Aqueous Humor in Glaucoma Secondary to Sturge-Weber Syndrome - Peng, Cheng; Wu, Yue; Ding, Xuming; Chen, Di; Zeng, Changjuan; Xu, Li; Guo, Wenyi (Frontiers in Immunology, 2020)
Glaucoma is one of the major causes of ocular morbidity in patients with Sturge-Weber syndrome (SWS). By using multiplex human cytokine antibody array, we simultaneously detected levels of 40 cytokines in the aqueous humor (AH) of patients with SWS-induced glaucoma (SG), or from patients with senile cataract as controls. Compared with the control group, levels of interleukin (IL)-12p40, macrophage inflammatory protein (MIP)-1d, IL-5, IL-7, interleukin-6 receptor (IL-6R), B lymphocyte chemoattractant (BLC), and tumor necrosis factor-alpha (TNF-a) in the AH were significantly higher in SG group. Samples from SG patients displayed significantly lower levels of MIP-1b, IL-6, MIP-1a and monocyte chemoattractant protein (MCP)-1 than controls. Further analysis showed that IL-7, MIP-1a, TNF-a were correlated with intraocular pressure (IOP) in patients with early-onset SG. Moreover, IL-12p40 was correlated with age in patients with SG. These cytokines may contribute to the immunopathogenesis or progression of glaucoma in patients with SG.